2012
DOI: 10.4995/wrs.2012.1231
|View full text |Cite
|
Sign up to set email alerts
|

Description of nestbox visits and suckling events in a group housing system for rabbit does as compared to individual cages

Abstract: AbstrAct:Research was conducted to study nursing associated events of lactating rabbit does. Nest box visits and suckling events were investigated using 6 group pens (8 does/pen) and 12 enriched individual cages. Each group pen and individual cage was observed by video for one day per week until weaning at 35 d of lactation, with exception of the third week of lactation. In the first 2 wk of lactation, videotapes were analysed for the frequency and duration of nest box visits per day. The fourth and fifth week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 18 publications
0
8
0
3
Order By: Relevance
“…Group-housed does show shorter and less frequent nest visits than single-housed ones and fewer suckling events are reported in that system (Rommers et al, 2012). We expected that later regrouping in the semi-group housing system would lead to higher growth rates of kits because the kits spent more time in close proximity to their mother.…”
Section: W O R L D R a B B I T S C I E N C Ementioning
confidence: 92%
See 1 more Smart Citation
“…Group-housed does show shorter and less frequent nest visits than single-housed ones and fewer suckling events are reported in that system (Rommers et al, 2012). We expected that later regrouping in the semi-group housing system would lead to higher growth rates of kits because the kits spent more time in close proximity to their mother.…”
Section: W O R L D R a B B I T S C I E N C Ementioning
confidence: 92%
“…Though in close proximity to their kits for a longer time (TG18 and TG22), the does did not seem to increase their nursing frequency. In fact, although single-housed does visit the nest more frequently than does in group housing (Rommers et al, 2012), they do not nurse their kits after every entry (Seitz et al, 1997in Schlolaut et al, 2013Coureaud et al, 2000). On the other hand, potentially less nursing in TG12 might be compensated by an earlier intake of regular feed due to the earlier access to fermented grass (silage) disposed in the common area.…”
Section: Kitsmentioning
confidence: 99%
“…En función de los resultados mencionados, el diseño de las experiencias para el estudio de las reproductoras en grupo ha evolucionado notablemente. Así, desde los trabajos iniciales caracterizados por el uso de recintos con cama de paja y grupos constituidos por dos, tres o cuatro conejas y presencia continua de un macho para conseguir monta natural espontánea (Hoy y Schuh, 2004; Ruis y Coenen, 2004;Szendrö et al, 2010), que normalmente acontece en el post-parto (Ruis, 2006;Szendrö et al, 2013), se ha pasado en la actualidad a la utilización de inseminación artificial, manejo en ciclos de 42 días mayoritariamente y posibilidades de identificación individual electrónica para que cada hembra pueda acceder a un único nidal (Ruis, 2006;Rommers et al, 2012). Asimismo, se ha cambiado de mantener a las reproductoras continuadamente en grupo al estudio del manejo en grupo temporal, es decir, las conejas comparten jaula en una fase del ciclo y en la otra fase cada coneja ocupa una jaula individual.…”
Section: Manejo De Las Reproductoras En Grupounclassified
“…La baja fertilidad se explica en parte por las pseudo-gestaciones antes mencionadas (23% en grupo vs. 0% en jaula individual) (Rommers et al, 2006). También se ha observado un menor número de gazapos vivos al nacimiento (Semigrupo: o inferior tamaño y/o peso de la camada al destete (Grupo: Ruis et al, 2005;Rommers et al, 2006;Semigrupo: Cervera et al, 2017), tal vez porque las hembras en grupo muestran amamantamientos cortos y con intervalos de más de 24h entre ellos, según constatan Rommers et al (2012). Como excepción, en el experimento en semigrupo de Machado et al (2016) se han hallado pesos al destete más elevados en los gazapos Tabla 1.…”
Section: Manejo De Las Reproductoras En Grupounclassified
“…The percentage of injured does was 21 and 17% in experiments 1 and 2, respectively. Rommers et al (2012) observed the nursing behaviour of does. The average duration of nursing events (nest box visits) was shorter (113 vs. 158 s, respectively) and the frequency of nursing was lower (1.9 and 2.6 per day, respectively) in group housing than in individual cages in the first 2 wk of lactation.…”
Section: Does Are Continuously Togethermentioning
confidence: 99%